Fluorophosphonates on‐Demand: A General and Simplified Approach toward Fluorophosphonate Synthesis. (12th March 2021) - Dutra, Jason K.; Foley, Timothy L.; Huang, Zhen; Fisher, Ethan L.; Lachapelle, Erik A.; Mahapatra, Subham; Ogilvie, Kevin; Butler, Todd W.; Bellenger, Justin; Devraj Majmudar, Jaimeen; am Ende, Christopher W.
Abstract: Herein, we report a general and simplified synthesis of fluorophosphonates directly from p ‐nitrophenylphosphonates. This FP on‐demand reaction is mediated by a commercially available polymer‐supported fluoride reagent that produces a variety (25 examples) of fluorophosphonates in high yields while only requiring reagent filtration for pure fluorophosphonate isolation. This reaction protocol facilitates the rapid profiling of serine hydrolases with diverse and novel sets of activated phosphonates with differential proteome reactivity. Moreover, slight modification of the procedure into a reaction‐to‐assay format has enabled additional screening efficiency. Abstract : Not too demanding : A robust and purification‐free, one‐step synthesis has been developed to enable the on‐demand preparation of structurally diverse fluorophosphonates from a stable, and storable "toolbox" of readily accessible p ‐nitrophenylphosphonates. Additionally, a reaction‐to‐assay protocol is highlighted that further facilitates the rapid screening of these valuable activity‐based probes.